Effects of treatment of paroxetine, bupropion or agomelatine on puberty onset, gonadotrophin and estradiol levels in female rats - Canpolat, S.; Ulker, N.; Yardimci, A.; Ozdemir, G.; Bulmus, O.; Ozcan, M.; Kelestimur, H. (Wiley-Blackwell, 2015)
[Abstract Not Available]